Performance study of an active-passive combined anti-frosting method for fin-tube heat exchanger. (15th August 2022) - Lyu, Ning; Shao, Zhibo; He, Hui; Wang, Feng; Liang, Caihua; Zhang, Xiaosong
Abstract: Superhydrophobic surface has demonstrated excellent anti-frosting and defrosting properties, but its effect is limited by monotonous passive application styles. In a novel active-passive combined frost suppression method for air source heat pumps, superhydrophobic modification and high-speed airflow (SMAF) are employed for frost suppression. In this work, the frosting-defrosting characteristics were experimentally studied for a fin-tube heat exchanger with the SMAF method applied under typical frosting conditions, and the results were compared with bare, hydrophilic, and superhydrophobic control groups. The influence of airflow parameters on the frost suppression effect was also revealed. Based on the experimental results, transient models for airflow parameters and frosting are established, a semi-empirical algorithm for heat exchanger performance under different anti-frosting methods is developed, and the adaptability of SMAF method to ambient temperature and humidity is revealed. The results show that the maximum net yield of the SMAF method can reach 97.9% and 18.7% respectively, compared with bare and superhydrophobic modification methods. Highlights: An anti-frosting method based on airflow and surface modification was proposed. A novel semi-empirical algorithm evaluating anti-frosting performance was developed. The method improved the heat transfer capacity of heat exchanger by 43.4%. The method reduced the defrosting heat consumption by 33.3%. The heat exchanger blockage time was delayed by 100%.